2023
DOI: 10.3390/ph16010074
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Lithium Therapy: Side Effects and Interactions

Abstract: Lithium remains the drug of first choice for prophylactic treatment of bipolar disorder, preventing the recurrences of manic and depressive episodes. The longitudinal experiences with lithium administration greatly exceed those with other mood stabilizers. Among the adverse side effects of lithium, renal, gastrointestinal, neurological, thyroid, metabolic, cognitive, dermatological, cardiologic, and sexual are listed. Probably, the most important negative effect of lithium, occurring mostly after 10–20 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Lithium therapy is the first choice of drug for the prophylactic treatment and management of recurrent bipolar illness, and manic and depressive episodes. 2 , 3 At a neuronal level, lithium decreases the excitatory but increases inhibitory neurotransmitters; however, multiple complex involvements of neurotransmitters are involved to achieve homeostasis. 4 The incidence of lithium toxicity based on a cohort study was found to be 0.01 per patient-year.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium therapy is the first choice of drug for the prophylactic treatment and management of recurrent bipolar illness, and manic and depressive episodes. 2 , 3 At a neuronal level, lithium decreases the excitatory but increases inhibitory neurotransmitters; however, multiple complex involvements of neurotransmitters are involved to achieve homeostasis. 4 The incidence of lithium toxicity based on a cohort study was found to be 0.01 per patient-year.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional pharmacotherapy for bipolar disorder typically involves the use of mood stabilizers, antipsychotics, and antidepressants, which can be effective in controlling symptoms but may have significant side effects [ 15 ]. Mood stabilizers such as lithium can cause side effects such as tremors, weight gain, and kidney damage, while antipsychotics may cause side effects such as sedation, weight gain, and movement disorders [ 16 ]. Antidepressants can also cause side effects such as insomnia, sexual dysfunction, and suicidal thoughts [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This region plays a role in the regulation of emotional control. Clinical evidence is building and suggests that TMS can be both efficacious and safe in the reduction of depressive symptomatology in bipolar II [ 16 ]. The ability to target specific areas of the brain with TMS makes it a promising option for the treatment of a range of mental illnesses and disorders [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations